Analisi Pengaruh Hutang Luar Negeri Terhadap Perekonomian Indonesia - Gilang Ramadani; Amanda Eka Saputri; Muhammad Yasin (Universitas 45 Surabaya, 2023)
This study aims to describe how Indonesia's foreign debt isdeveloping, the impact of foreign debt on the Indonesian economy and what alternative policies can be taken to mitigate the negative impact of foreign debt on the Indonesian economy. This type of research is descriptive qualitative research. The data collection technique used is observation and study of documents/documentation. Documentary research is a data collection technique for conducting a review of books, documents, records, and reports relating to a problem to be handled. The research data was obtained from various government agency publications such as Bank Indonesia, the Central Bureau of Statistics and the Ministry of Finance of the Republic of Indonesia. The results of the study show that external debt (ULN) can drive Indonesia's economic growth in industries that absorb high external debt (ULN). Domestic savings play an increasingly important role.